Immunohistochemical scoring of LAG-3 in conjunction with CD8 in the tumor microenvironment predicts response to immunotherapy in hepatocellular carcinoma - Cheung, Chun Chau Lawrence; Seah, Yong Hock Justin; Fang, Juntao; Orpilla, Nicole Hyacinth Calpatura; Lau, Mai Chan; Lim, Chun Jye; Lim, Xinru; Lee, Justina Nadia Li Wen; Lim, Jeffrey Chun Tatt; Lim, Sherlly; Cheng, Qing; Toh, Han Chong; et al. (Frontiers in Immunology, 2023)
Introduction Immune checkpoint blockade (ICB) is a systemic therapeutic option for advanced hepatocellular carcinoma (HCC). However, low patient response rates necessitate the development of robust predictive biomarkers that identify individuals who benefit from ICB. A 4-gene inflammatory signature, comprising CD8, PD-L1, LAG-3, and STAT1, was recently shown to be associated with a better overall response to ICB in various cancer types. Here, we examined whether tissue protein expression of CD8, PD-L1, LAG-3, and STAT1 predicts response to ICB in HCC. Methods HCC samples from 191 Asian patients, including resection specimens from 124 patients (ICB-naïve) and pre-treatment specimens from 67 advanced HCC patients treated with ICB (ICB-treated), were analyzed for CD8, PD-L1, LAG-3, and STAT1 tissue expression using multiplex immunohistochemistry followed by statistical and survival analyses. Results Immunohistochemical and survival analyses of ICB-naïve samples showed that high LAG-3 expression was associated with shorter median progression-free survival (mPFS) and overall survival (mOS). Analysis of ICB-treated samples revealed that high pre-treatment LAG-3+ and LAG-3+CD8+ cell proportions were most closely associated with longer mPFS and mOS. Using log-likelihood model, adding the total LAG-3+ cell proportion to the total CD8+ cell proportion significantly increased the predictive values for mPFS and mOS, compared with total CD8+ cell proportion alone. Moreover, levels of CD8 and STAT1, but not PD-L1, were significantly correlated with better responses to ICB. After separately analyzing viral-related and non-viral HCC samples, only the LAG3+CD8+ cell proportion was significantly associated with responses to ICB regardless of viral status. Conclusion Immunohistochemical scoring of pre-treatment levels of LAG-3 and CD8 in the tumor microenvironment may help predict ICB benefits in HCC patients, using readily translatable immunohistochemistry-based techniques in the clinical setting.